Tracheal pseudo-tumor caused by herpes simplex virus - Katsenos, Stamatis; Sampaziotis, Dimitrios; Archondakis, Stavros (Multidisciplinary Respiratory Medicine, 2013)
Background: Herpes simplex virus (HSV) has been shown to cause respiratory tract infections mostly in severely immunocompromised patients. Endobronchial tumor-like lesions have been described very rarely as HSV pulmonary manifestations in critically ill patients or in immunosuppressed individuals. Case presentation: This case study describes a 75-yr-old male who presented with persistent hoarseness. Fiberoptic bronchoscopy showed marked mucosal thickening protruding in mid and distal trachea causing stenosis. Biopsy specimens demonstrated cytopathological changes consistent with HSV type 1 and 2 infection. Conclusions: To the best of the authors’ knowledge, this is the first reported case of HSV presenting as an endotracheal tumor in an immunocompetent person.